Response of Rhizobacterial Community to Biochar Amendment in Coal Mining Soils with Brachiaria Decumbens as Pioneer Plant. Issue 1 (2nd January 2020) - Rios Montes, Karina; Pino, Nancy J.; Peñuela, Gustavo A.; Mendoza, Alberto
ABSTRACT: Biochar has been used as an amendment for disturbed soils. However, the changes of the rhizobacterial community after the biochar addition in mine soils, has not yet been elucidated. The aim of this study was to evaluate the response in the rhizobacterial communities of Brachiaria decumbens during different reclamation processes of coal mining using biochar. Five treatments were carried out: control, mine soil + biochar, mine soil + biochar + Azospirillum brasilense, mine soil + biochar + arbuscular mycorrhizal fungal + Mortierella sp. DNA from the rhizospheric soil was sequenced by Ion Torrent. The relative abundance in each sample was calculated. The Proteobacteria (70%) and Actinobacteria (23%) phyla dominated the rhizobacterial community composition during the establishment time. Seven months after seeding, Actinobacteria decreased significantly, while Proteobacteria increased. The Acidobacteria phylum was higher in the control. There was a higher abundance of Proteobacteria with the biochar treatments than for the control, thus the baseline for the rhizobacterial community changes induced by biochar was provided. The alpha diversity index showed the effect of biochar on the diversity and dominance of the rhizobacterial communities. The hierarchical clustering tree showed a correlation between the treatments with biochar, and a significant differentiation between these and the control treatment.